Association of biosecurity and hygiene practices with avian influenza A/H5 and A/H9 virus infections in turkey farms - Islam, Ariful; Islam, Monjurul; Dutta, Pronesh; Rahman, Md Ashiqur; Al Mamun, Abdullah; Khan, AKM Dawlat; Samad, Mohammed Abdus; Hassan, Mohammad Mahmudul; Rahman, Mohammed Ziaur; Shirin, Tahmina (Frontiers in Veterinary Science, 2024)
High pathogenicity avian influenza (HPAI) H5N1 outbreaks pose significant threat to the health of livestock, wildlife, and humans. Avian influenza viruses (AIV) is enzootic in poultry in many countries, including Bangladesh, necessitating improved farm biosecurity measures. However, the comprehension of biosecurity and hygiene practices, as well as the infection of AIV in turkey farms, are poorly understood in Bangladesh. Therefore, we conducted this study to determine the prevalence of AIV subtypes and their association with biosecurity and hygiene practices in turkey farms. We collected oropharyngeal and cloacal swabs from individual turkeys from 197 farms across 9 districts in Bangladesh from March to August 2019. We tested the swab samples for the AIV matrix gene (M gene) followed by H5, H7, and H9 subtypes using real-time reverse transcriptase-polymerase chain reaction (rRT-PCR). We found that 48.73% (95% CI: 41.56-55.94) of turkey farms were AIV positive, followed by 19.29% (95% CI: 14.03-25.50) for H5 Deleted: ¶ 32 Deleted: Avian Influenza Virus (AIV) is a zoonotic virus